2011
DOI: 10.1055/s-0030-1268446
|View full text |Cite
|
Sign up to set email alerts
|

Reduktion des Alkoholkonsums und Förderung der Rauchabstinenz bei Jugendlichen und jungen Erwachsenen mittels Internet und Mobiltelefon: ein Literaturüberblick

Abstract: Zusammenfassung Ziel derstudies that aimed at decreasing alcohol consumption by the use of the Internet were conducted in college or university students from the United States or New Zealand and the majority of these studies were based on the social norms approach. Good empirical evidence exists concerning the efficacy of web-based social norms interventions to decrease alcohol consumption in students. In the field of smoking cessation, Internet interventions are much more heterogeneous concerning the target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…We report findings from four reviews evaluating digital platforms for substance abuse among adolescents [67] , [68] , [69] , [70] . A review evaluating the impact of Internet-based programs and intervention delivered via CD-ROM targeting alcohol, cannabis, and tobacco suggests that these programs have the potential to reduce alcohol and other drug use as well as intentions to use substances in the future [67] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report findings from four reviews evaluating digital platforms for substance abuse among adolescents [67] , [68] , [69] , [70] . A review evaluating the impact of Internet-based programs and intervention delivered via CD-ROM targeting alcohol, cannabis, and tobacco suggests that these programs have the potential to reduce alcohol and other drug use as well as intentions to use substances in the future [67] .…”
Section: Resultsmentioning
confidence: 99%
“…Web-based interventions for problematic substance use by adolescents and young adults highlighted insufficient data to assess the effectiveness of Web-based interventions for tobacco use by adolescents [68] . For Internet and mobile phone use, one review suggested good empirical evidence concerning the efficacy of Web-based social norms interventions to decrease alcohol consumption in students [69] . Internet interventions for smoking prevention are found to be heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
“…The web-based part of the intervention provides normative feedback based on the social norms approach [12], which constitutes the theoretical background of the majority of evidence based internet interventions to reduce problem drinking in young people [15, 28]. …”
Section: Methodsmentioning
confidence: 99%
“…The alcohol intervention provides normative feedback based on the social norms approach [21], which constitutes the theoretical background of the majority of evidence-based internet interventions to reduce problem drinking in young people [23, 24]. …”
Section: Methods and Designmentioning
confidence: 99%